Some New Exact Solutions for Prescribed Vorticity Distribution of Couple Stress Fluids in the Presence of Unknown Body Force - Rana Khalid Naeem (Journal of Basic & Applied Sciences, 2021)
In the present paper, we indicate some new exact solutions of equations of motion for plane steady incompressible couple stress fluids flows in the presence of unknown body force for which vorticity distribution is defined by Eq. (12). All solutions involve arbitrary real constants and arbitrary real constants depending on the parameter èindicating that a large number of streamfunctions and expressions for body force can be constructed. Some streamfunctions ø are constructed for some values of parameters. The streamlines patterns of these streamfunctions are presented and discussed.